Tension-type headache in the Emergency Department Diagnosis and misdiagnosis: The TEDDi study - García-Azorín, D.; Farid-Zahran, M.; Gutiérrez-Sánchez, M.; González-García, M. N.; Guerrero, A. L.; Porta-Etessam, J. (Scientific reports, 2020)
Headache is a common reason to visit the emergency department (ED). Tension-type headache (TTH) is the commonest headache. The diagnosis of TTH implies a mild condition, with no need for special tests. We evaluated the use of the International Classification of Headache Disorders (ICHD) criteria for TTH in the ED. We performed a cross-sectional study including all ED patients with a definite TTH diagnosis in their discharge report for 2.5 years. We evaluated whether the ICHD criteria for TTH were referenced and met. We analysed discrepancies concerning anamnesis or prior history and reclassified patients. A total of 211 out of 2132 patients fulfilled the criteria (9.9%). Only five patients fulfilled TTH criteria. Criteria A-D were referenced in 60–84% of patients and met in 16–74% of these patients. Anamnesis was discrepant in 87.5% as was prior history in 20.8%. After re-reclassification, 21 patients fulfilled the criteria for TTH (five) or probable TTH (16). In 106 patients, another headache was diagnosed, with migraine in 40 (18.9%), secondary headache in 64 (30.3%), and a life-threatening disorder in 13 (6.1%). In our sample, TTH was overdiagnosed. Only a minority of patients fulfilled the ICHD criteria. Inconsistencies in prior medical history or anamnesis were frequent.